A method to measure the denatured proteins in the corona of nanoparticles based on the specific adsorption of Hsp90ab1. Issue 29 (22nd July 2020) - Liu, Shang; Jiang, Xinbang; Tian, Xuejiao; Wang, Zhenzhen; Xing, Zhen; Chen, Jiahui; Zhang, Junfeng; Wang, Chunming; Dong, Lei
Abstract : The specific adsorption of Hsp90ab1 is exploited to assess the protein denaturation in the biological corona of nanoparticles. Abstract : The protein corona influences and determines the biological function of nanoparticles (NPs) in vivo . Analysis and understanding of the activities of proteins in coronas are crucial for nanobiology and nanomedicine research. Misfolded proteins in the corona of NPs theoretically exist, and a protein denaturation-related cellular response might occur in this process as well as in related diseases. The exact evaluation of protein denaturation in the corona is valuable to assess the bioactivities of NPs. Here, we found that the level of adsorbed heat shock protein 90 kDa α class B member 1 (Hsp90ab1) by the denatured protein in iron–cobalt–nickel alloy NPs (FeCoNi NPs) and iron oxide NPs (Fe3 O4 NPs) was correlated with circular dichroism (CD) analysis and 1-anilinonaphthalene-8-sulfonate (ANS) analysis. The content of Hsp90ab1 in the corona could be easily analysed by western blotting (WB). Further analysis suggested that the method could precisely show the time-dependent protein denaturation on Fe3 O4 NPs, as well as the influence of the size and the surface modification. More importantly, this method could be applied to other proteins, like lysozyme, other than albumin. Based on the results and the correlation analysis, incubation and detection of Hsp90ab1 in the NP–corona complex can be used as a new and feasible method to evaluate protein denaturation induced by NPs.